Microsuspension of an Antibiotic, Design Statistical Analysis and Optimization - Chandira, Rajappa Margret; Pethappachetty, Palanisamy; Vijayasankar, Gudanagaram Ramamoorthy; Tamilarasan, Nallaiya (Asian Journal of Biological and Life Sciences)
An attempt has been made in this study for formulation and evaluation of ofloxacin Microsuspension by adding excipients in formulations. It can be given by any route due to its rapid disintegration rate. The performance of biological systems has improved. Suspensions are more chemically stable than solutions. It can be used for drugs that are poorly water-soluble and administered via any method. The physicochemical characterization for a pure drug such as organoleptic properties, spectral analysis UV spectroscopic studies, ATR-FTIR and DSC were investigated and confirmed. Various formulations of ofloxacin micro-suspension were formulated by using SLS, PVP and Urea in different concentrations by the micro-precipitation method. The prepared micro-suspension has a smooth surface morphology and is spherical at 200nm. The Microsuspension were evaluated for physical characterization, pH, drug loading, sedimentation volume, viscosity, particle size, in vitro drug release and the stability studies carried out for the optimized formulation.
Keywords: Bioavailability; Enhance absorption; Micro-Precipitaion method; Microsuspension; Ofloxacin